An overlooked risk for skin health: Less availability and higher cost of sunscreen for people with melanated skin - Emerson D. Basch; Grace C. Hillyer (Dialogues in Health)
Background: Sunscreen with a skin protection factor (SPF) of 30 or greater is recommended to reduce the risk of skin cancer and improve skin health for all people regardless of skin tone. Traditional sunscreen that creates a white cast on the skin is incompatible with melanated skin. Methods: The number of products on the shelf, SPF level, application, coloration, and cost were recorded at three beauty supply chain stores and three pharmacy, health, and wellness stores in or near Harlem in New York City in the Spring of 2023. The number of skin tones for tinted sunscreen was visually matched to the Fitzpatrick Skin Phototypes scale. Results: A total of 385 sunscreen products were identified; 78.7 % were traditional white sunscreen, followed by sheer (15.3 %) and tinted (6.0 %) products. Beauty supply stores offered more tinted sunscreen options than did pharmacy, health, and wellness stores (n = 17,15.3 % vs. n = 6, 2.2 %, p < 0.001). Of the tinted sunscreen products, 19 brands offered only a single tone. Tinted sunscreen was significantly more expensive with an average cost of $24.59 [SD $14.71] per ounce vs. $6.85 [SD 8.66] for traditional, and $9.38 [SD 8.92] for sheer suncreen. Conclusions: Sunscreen that is tinted or sheer and compatible with melanated skin is less available and more costly than traditional white sunscreen in beauty and pharmacy chain stores in NYC. Availability and affordability of sunscreen matching the spectrum of skin tones are essential for optimal sun protection and skin health.